2021
DOI: 10.1111/jrh.12580
|View full text |Cite
|
Sign up to set email alerts
|

Rural and racial disparities in colorectal cancer incidence and mortality in South Carolina, 1996 – 2016

Abstract: Purpose: Colorectal cancer (CRC) is the third leading cause of cancer mortality among men and women in the United States and South Carolina (SC). Since SC has one of the highest proportions of Black (27.9%) and rural residents (33.7%), the purpose of this investigation was to describe the burden of CRC on racial disparities in rural populations.Methods: Count data from 2012 to 2016 were obtained from the state central cancer registry using an online data retrieval system. Rural-urban status was determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This work was not focused on CRC but it provides in-depth and valuable insight regarding the social determinants of health at play in these populations and how those determinants of health may work together to affect cancer outcomes. Adams et al 19 investigated trends in incidence and mortality of CRC across racial and rural-urban populations. Their study found CRC mortality decreased over time in all racial and geographic groups with the exception of the rural Black population.…”
Section: Discussionmentioning
confidence: 99%
“…This work was not focused on CRC but it provides in-depth and valuable insight regarding the social determinants of health at play in these populations and how those determinants of health may work together to affect cancer outcomes. Adams et al 19 investigated trends in incidence and mortality of CRC across racial and rural-urban populations. Their study found CRC mortality decreased over time in all racial and geographic groups with the exception of the rural Black population.…”
Section: Discussionmentioning
confidence: 99%
“…Facilities and services essential for cancer treatment, such as laboratories and radiation therapy, are also more sparse in rural areas 3 . Therefore, rural residents often need to travel long distances to obtain cancer screening, diagnosis, and treatment 2–8 . Rural patients' access to care is further aggravated by low socioeconomic status, lack of insurance coverage, 8 weather‐associated road conditions, and lack of public transportation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Rural patients' access to care is further aggravated by low socioeconomic status, lack of insurance coverage, 8 weather-associated road conditions, and lack of public transportation. 7 These rural-urban differences lead to disparities in the utilization of cancer screening services as well as the use of adjuvant therapy. 8 Differential access and utilization of cancer-related services are important metrics due to their association with negative cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer services are underused by rural residents in the United States (US) [ 1 ]. Rural residents often need to travel long distances to obtain cancer screening, diagnostic services, and treatment, and weather-associated road conditions and lack of public transportation may further impede care [ 2 ]. Additionally, healthcare accessibility, especially specialized cancer care, is aggravated by low socioeconomic status and lack of health insurance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%